(untitled) (Journal of Economics and Sustainability, 2022)
The fisheries sector is a vital sector for Southeast Asian (ASEAN) nations as it provides a source of protein and employment to the people. However, the ASEAN fisheries sector also encounters severalconflict issues. Fisheries conflicts are common in Southeast Asian nations and are dangerous if left unaddressed. Such conflicts can destroy the livelihoods of fishers and negatively affect food security and the fishing environment. In this paper, fisheries conflicts cases in ASEAN are used to examineconflicts faced by fishers. The objective is to understand the sources of conflicts and recommend approaches for reducing or eliminating the conflicts to ensure the sustainability of fisheries resources in the ASEAN region. The main findings of this paper show that the principal sources of conflicts in ASEAN are disagreement of fishers with the allocation of resources by the government and competition among fishers for the limited fisheries resources. Community-based management or co-managed fisheries have the potential to empower communities in decision making to solve the conflicts and ensure fisheries rights are allocated equitably.